ANALISIS PENDAPATAN NELAYAN BAGAN PERAHU DI KABUPATEN KEPULAUAN SELAYAR MASMULYADI - Masmulyadi Masmulyadi; Sri Widodo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2014)
This study aim to know level of income and business profit of lift nets boat and the factors that affect the income of fisherman’s boat lift nets in Selayar District. The hypothesis is (1) fisherman’s boat lift nes is business profitable, (2) estimated operating revenues of boat lift fisherman affected by the intensity factor to sea fishing intensity, family dependent age, education, business experience, hauling and capital.This research uses descriptive analytical method. The sample used in this study is the fisherman who use fishing gear fisherman’s light fishing boat of 30 who simple random. The analysis used is farm management analysis and regression analysis.The result showed that the fishing affect by fishermen’s using the boat in one period light fishing arrest financially beneficial to the averagevincome of Rp 9.817.139 and the value of the RC ratio was 1,32. While the factors influencing income is the intensity of fishing bots at sea fishing intensity, family dependent, age, education, business experience, hauling and capital.